Hungarian Monitoring, 13 July 1989 . [Magyar rádiófigyelő], 1989. július 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - International reactions to Bush's Budapest visit - Financiers' summit in Paris - Genscher in Prague - Bicentenary celebrations begin in Paris - Gabčíkovo-Nagymaros dam a main topic in Czechoslovak government spokesman's press conference Domestic Affairs: - At János Kádár's catafalque - Thoughts on János Kádár's life - Hungarian October Party and Hungarian Radical Party want to hold demonstration in Ferenc Münnich Street tomorrow - Draft law on former internees already being formed in government circles Economy: - National Artisans’ Association (KIOSZ) on using USD 25 million promised by Bush - Opposition opinions on the chances of American economic assistance - Hungarian-Soviet trade accounts - First Hungarian investment fund starts fund accumulation and share registry - New regulations on citizens' foreign currency management Külpolitika: - Bush elnök budapesti látogatásának külföldi visszhangja - A párizsi tőkés csúcs - Genscher Prágában - Megkezdődtek Párizsban a bicentenárium ünnepségei - A CS kormányszóvivő sajtóértekezletének egyik fő témája a Bős-nagymarosi vízlépcső volt Belpolitika: - Kádár János ravatalánál - Gondolatok Kádár János életútjáról - A Magyar Október Párt és a Magyar Radikális Párt holnap tüntetést akar tartani a Münnich Ferenc utcában - Kormányzati körökben már formálódik az egykori internáltakról szóló törvénytervezet Gazdaság: - A KIOSZ a Bush által ígért 25 millió dollár felhasználásáról - Ellenzéki vélemények az amerikai gazdasági segély lehetőségéről - Magyar-szovjet kereskedelmi elszámolás - Megkezdődött az első magyar befektetési alap tőkegyűjtési és részvény jegyzési akciója - A lakosság devizagazdálkodásának új szabályairól